Canada : Financial System Stability Assessment-Update. (IMF Staff Country Reports; Country Report, 2008)
The Canadian financial sector is among the world's most highly developed. The five large banking groups that form the core of the system are conservatively managed and highly profitable. The stress tests suggest that the large Canadian banks can withstand a broad range of shocks. The current turbulence in global credit markets has affected Canada's asset-backed commercial paper market. The Canadian Depository Securities Settlement System is sound, efficient and reliable, and it complies with almost all Recommendations for Securities Settlement Systems.